2017
DOI: 10.3892/ol.2017.7602
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the novel susceptibility loci for prostate cancer in a Chinese population

Abstract: Abstract. The present study evaluated 23 newly identified susceptibility loci for prostate cancer (PCa) in a Chinese population and assessed whether any validated loci were associated with the genetic risk score (GRS) of PCa in a Chinese population. A total of 1,417 patients with PCa and 1,008 controls were recruited in the present study. The association of each single nucleotide polymorphism (SNP) with PCa risk and PCa aggressiveness was analyzed. The predictive ability of two GRSs based on 30 SNPs (GRS30) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Up to now, conclusions on etiology of prostate carcinogenesis is still inconsistent. In recent decades, researchers pay more attention to the relationship between single‐nucleotide polymorphism and cancer susceptibility, including PCa . Previous clinical studies and in vitro experiments showed evidence that CDKN1B is a significant tumor suppressor gene in the development of PCa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, conclusions on etiology of prostate carcinogenesis is still inconsistent. In recent decades, researchers pay more attention to the relationship between single‐nucleotide polymorphism and cancer susceptibility, including PCa . Previous clinical studies and in vitro experiments showed evidence that CDKN1B is a significant tumor suppressor gene in the development of PCa .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, researchers pay more attention to the relationship between singlenucleotide polymorphism and cancer susceptibility, including PCa. [31][32][33] Previous clinical studies and in vitro experiments showed evidence that CDKN1B is a significant tumor suppressor gene in the development of PCa. 25,34 Several polymorphisms of CDKN1B gene have been reported to be correlated with PCa risk, however, only the Val 109 Gly variant located in exon area could lead to one amino acid change.…”
Section: Discussionmentioning
confidence: 99%
“…Since these SNPs exhibited a cumulative effect on PCa risk, several polygenic risk score (PRS) methods have been used for measuring the cumulative association of SNPs 4 . The PRS derived from PCa risk‐associated SNPs based on different populations were well‐established and able to evaluate an individual's risk of PCa in previous studies 5–8 . It could be used either for inherited risk assessment among general population or help differentiate the individuals at higher risk of positive biopsies in biopsy cohorts as an add‐on to PSA and other examinations.…”
Section: Introductionmentioning
confidence: 99%
“…4 The PRS derived from PCa riskassociated SNPs based on different populations were well-established and able to evaluate an individual's risk of PCa in previous studies. [5][6][7][8] It could be used either for inherited risk assessment among general population or help differentiate the individuals at higher risk of positive biopsies in biopsy cohorts as an add-on to PSA and other examinations. A population-standardized PRS is calculated by multiplying by all SNPs and each SNP is standardized against the general population, so its expected mean value shall always be 1.0 in a general population, regardless of the number of SNPs included in the calculation.…”
Section: Introductionmentioning
confidence: 99%